ANALYSIS OF RESEARCH RESULTS OF ISLAMIC EDUCATION A PHILOSOPHICAL APPROACH - Muhamad Fajri; Abdul Mujib (Jurnal Al-Fatih, 2022)
The importance of developing Islamic education through research with various approaches, especially philosophical approaches, it is necessary to update the discussion and planning prospects for the development of Islamic education research, so that research and Islamic education are not stagnant and left behind. So this study aims to analyze the results of research on Islamic education that uses a philosophical approach and analyze the scope of Islamic education that needs to be developed through research that uses a philosophical approach in the future. This study uses two methods, namely netnography to answer the first research objective, and a descriptive approach to literature research to answer the second research objective. The analytical technique used in this research is philosophical-critical analysis. This study shows that (1) Islamic education research with a dominant philosophical approach uses library research methods and focuses on examining the ontology and axiology sides, such as the philosophy of goals, principles and basics of Islamic education, so (2) Islamic education research with a philosophical approach needs to be developed in the future. epistemological studies, such as teaching materials, materials, methods and evaluation of learning, thus the use of research methods is more of a field research to reveal the empirical reality of Islamic education.